2006
DOI: 10.1038/nsmb1069
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of gating at the potassium-channel selectivity filter

Abstract: We show that in the potassium channel KcsA, proton-dependent activation is followed by an inactivation process similar to C-type inactivation, and this process is suppressed by an E71A mutation in the pore helix. EPR spectroscopy demonstrates that the inner gate opens maximally at low pH regardless of the magnitude of the single-channel-open probability, implying that stationary gating originates mostly from rearrangements at the selectivity filter. Two E71A crystal structures obtained at 2.5 A reveal large st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
503
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(541 citation statements)
references
References 49 publications
36
503
2
Order By: Relevance
“…We hypothesize the presence of a gating charge at the selectivity filter of the CRAC channel. A similar phenomenon is observed in the KcsA K ϩ channel, where the reorientation of the Glu 71 residue in the electric field induces destabilization of the inactivated conformation of the channel pore (39,40). Our results, however, suggest that the gating charge assumes a position that stabilizes the open channel conformation (destabilizes the closed conformation) at negative voltages.…”
Section: Analysis Of the Crac Channel Selectivity By Co-expression Ofsupporting
confidence: 82%
“…We hypothesize the presence of a gating charge at the selectivity filter of the CRAC channel. A similar phenomenon is observed in the KcsA K ϩ channel, where the reorientation of the Glu 71 residue in the electric field induces destabilization of the inactivated conformation of the channel pore (39,40). Our results, however, suggest that the gating charge assumes a position that stabilizes the open channel conformation (destabilizes the closed conformation) at negative voltages.…”
Section: Analysis Of the Crac Channel Selectivity By Co-expression Ofsupporting
confidence: 82%
“…Under steady-state conditions, KcsA exhibits a low open probability (P O ) because most of the time it resides in a C-type inactivated state (12,(33)(34)(35). It was previously shown that anionic phospholipids may increase P O , providing a more favorable environment for the open state of KcsA (36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…Upon activation at acidic pH, KcsA mediates a transient K þ current that is characterized by a fast activation time course followed by a slow C-type inactivation process (12). This time course is well described by a successive and coordinate opening and closing of activation and inactivation gates within the conduction pathway of the KcsA channel ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such conformational transitions regulate the flow of potassium ions across the membrane (6-9), a process underlying many fundamental biological processes, in particular the generation of nerve and muscle action potentials (10). These conformational changes, moreover, play a fundamental role in mediating coupling between the voltage-sensor, activation gate and selectivity filter elements of Kv channels (6)(7)(8)(9)(11)(12)(13)(14).Amenable to rapid and highly accurate functional characterization without the need for protein purification, the Kv channel represents an excellent model for studying the features underlying allosteric communication networks in proteins. Recent systematic energy perturbation analysis of the pore domain of the archetypal Shaker Kv channel (15) revealed that gating-sensitive positionsi.e., those positions where mutation dramatically affects the closedopen equilibrium of the channel-cluster around the channel activation gate and near the selectivity filter functional elements, when mapped onto the closed channel pore structure (Fig.…”
mentioning
confidence: 99%